Level of AI Dependency Vis-à-Vis Study Habits Among College Students at Quezon City University (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study examined the level of Artificial Intelligence (AI) dependency among college students at Quezon City University (QCU) and its relationship with their study habits. Using a descriptive-correlational research design, data were gathered from 372 respondents across five colleges through a validated survey questionnaire. The study assessed AI dependency across four dimensions, frequency and duration of AI tool usage, reliance on AI for academic tasks, compulsive or habitual use of AI tools, and interference of AI usage with independent learning, and study habits across four dimensions: time management and study scheduling, consistency and regularity of review, use of study strategies and techniques, and level of focus and concentration during study sessions. Findings revealed that students demonstrated a moderate level of AI dependency and a moderate-to-agreeable level of study habits. Significant differences in AI dependency were observed when respondents were grouped by demographic profile. Notably, a significant relationship was found between AI dependency and study habits, suggesting that increasing AI dependency is associated with changes in students' approach to academic work. The study recommends institutional policies and instructional strategies to promote responsible and balanced AI use in higher education